Fracture resistance of composite resin cores with or without prefabricated posts over different substrates - De Queiroz, Vanessa Salvadego; Pizi, Eliane Cristina Gava; Carlos Jose, Soares; Vanessa Cruz, Macedo [UNESP]; Luis Roberto Marcondes, Martins (My University, 2011)
The fracture resistance of endodontically treated teeth has been an obstacle to the durability of the remaining teeth and restorations. The aim of this study was to evaluate the fracture resistance of endodontically treated bovine and human teeth that were restored with either prefabricated metal posts, glass fiber posts, or composite resin cores. Statistical analysis revealed significant difference between different substrates, but there was no statistically significant difference between different types of intraradicular posts or in the interaction between substrate and post types. The intraradicular posts do not increase the fracture resistance of endodontically treated teeth. The metal posts presented more unfavorable fracture modes when compared to glass fiber posts and composite resin cores.
Keywords: glass; glass fiber; metal; resin; analysis of variance; animal; cattle; comparative study; dental procedure; human; nonparametric test; pathophysiology; periodontal ligament; physiology; tooth crown; tooth fracture; tooth pulp disease; Analysis of Variance; Animals; Cattle; Composite Resins; Crowns; Dental Models; Glass; Humans; Metals; Periodontal Ligament; Post and Core Technique; Statistics, Nonparametric; Tooth Fractures; Tooth, Nonvital